(untitled) (Journal of the Sociology and Theory of Religion, 2025)
Religion plays a fundamental role for human beings, there is no human society that lacks something that social scientists would call religion. This plays an important role in the lives of many people in issues such as the existence of the soul or its destiny. For its part, Catholic tradition considers that one of the destinations of the soul is Purgatory and indicates that it is possible to pray for the souls found here so that they can reach Heaven. In this article, the feasibility of saving all souls from Purgatory has been calculated, through mathematical reasoning and considering aspects of the human condition.